The Potential Impact of Renin-Angiotensin System Inhibitors on Cancer Survival and Recurrence: A Systemic Review and Meta-Analysis - Fatima, Kaneez; Ellahi, Aayat; Adil, Mariam; Kashif, Haider; Uzair, Muhammad; Ashraf, Naela; Barolia, Mehak; Hyder, Mujtaba; Nakhuda, Areeba; Ayub, Michelle; Butt, Sofia Jamil; Rashid, Ahmed Mustafa (Journal of cardiovascular pharmacology, 2025)
Renin-angiotensin system inhibitors (RASis), specifically angiotensin-converting enzyme inhibitors (ACEis) and angiotensin II receptor blockers (ARBs), are widely used antihypertensives. Their impact on the prognostic outcomes among patients with cancer has been subject to scrutiny and debate. The aim of this study was to evaluate the effect of RASis on survival in patients with cancer.We systematically searched PubMed, Web of Science, Embase, and Cochrane Library for relevant studies published until April 1, 2022. All the studies, interventional or observational, which examined effects of ARBs and ACEis on cancer prognosis compared with a control group and reported the survival outcomes and hazard ratios were included in the analysis. From each study, pooled hazard ratios (HRs) with corresponding 95% confidence intervals (95% CIs) were identified and collected. Subgroup analysis was conducted to investigate heterogeneity.61 studies were included in this meta-analysis. Data of 343,283 participants were used in the study. It was found that RASis improved overall survival (HR = 0.88; 95% CI, 0.82-0.93; P < 0.0001), progression-free survival (HR = 0.72; 95% CI, 0.65-0.79; P < 0.00001), disease-specific survival (HR = 0.86; 95% CI, 0.71-1.04; P = 0.03), and recurrence-free survival (HR = 0.74; 95% CI, 0.58-0.93; P = 0.01) in patients with cancer. The effect of RASis on overall survival varied depending on the type of cancer or type of RASis (ACEis or ARBs), according to subgroup analysis.The usage of renin-angiotensin system inhibitors has a positive impact on survival outcomes and recurrence among patients with cancer.